Ameloblastoma: A succinct review of the classification, genetic understanding and novel molecular targeted therapies. Issue 4 (August 2021) - Shi, Hongyi Adrian; Ng, Chee Wee Benjamin; Kwa, Chong Teck; Sim, Qiu Xia Chelsia
Abstract: Ameloblastomas are benign but locally invasive neoplasms which may grow to massive proportions and cause significant morbidity. Although some types of ameloblastoma can be treated predictably with aggressive surgical treatment, recurrent ameloblastoma and metastasising ameloblastoma are still difficult to treat. Recent studies have identified recurrent somatic and activating mutations in the mitogen-activated protein kinase (MAPK) and sonic hedgehog (SHH) signalling pathways in ameloblastoma. This development provided a possibility that molecular targeted therapies can be used as neoadjuvant treatment. In this review, we provide a summary of the latest WHO classification of ameloblastoma, the current understanding of genetic mutations and novel molecular targeted therapies arising from the recent developments. Highlights: An updated classification of ameloblastoma by the WHO in 2017. Mutations in MAPK and SHH pathways have been identified in ameloblastoma. BRAF V600E mutation is the most common (43%–82% of ameloblastomas). Molecular targeted therapies using BRAF and/or MEK inhibitors appear promising.